The status of mangrove ecosystems on Keter Island, Tembeling Waters, Bintan Regency, Riau Islands - Lubis, Latif; Lestari, Febrianti; Susiana, Susiana; Rochmady, Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
Keter Island, located in Tembeling Tanjung Village, Bintan Regency, harbors a diverse mangrove ecosystem, predominantly composed of Rhizophora species. This study aimed to assess mangrove density at the tree level, evaluate vegetation cover, and determine the ecological status of the mangrove ecosystem based on its level of degradation. Field surveys were conducted to obtain an overview of ecosystem conditions, followed by systematic random sampling at sites within Tembeling waters where mangroves are distributed. The results indicate that mangrove tree density falls within the medium category, while canopy cover is classified as very dense with good ecological quality. Overall, the mangrove ecosystem on Keter Island is categorized as moderate, although it still displays favorable ecological characteristics. These findings suggest that while the mangrove ecosystem remains in a medium condition, degradation is ongoing, thereby necessitating further research and rehabilitation efforts. Given the vital role of mangroves in sustaining the ecological balance of small islands, direct monitoring and intervention by relevant authorities are essential to reduce degradation and ensure the long-term sustainability of the mangrove forest on Keter Island.